DETERMINAN CASH HOLDING PADA PERUSAHAAN SEKTOR KONSUMEN PRIMER DI INDONESIA - Patrick, Jonathan; Sufiyati, Sufiyati (Jurnal Paradigma Akuntansi, 2025)
The purpose of this research was conducted to find empirical evidence about the effect of profitability, leverage, sales growth, capital expenditure, and firm size on cash holdings in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The research model was analyzed using the Random Effect Model (REM). The samples used in this study were 63 primary consumer sector companies that had been selected by purposive sampling method for three years. Data processing was processed by multiple regression analysis of panel data using the Eviews SV 12. The results of this research show that leverage has a significant negative effect on cash holdings, and profitability, sales growth, capital expenditure, and firm size have no significant impact on cash holdings. The implication of this study is that companies can manage the amount of company cash for operational activities.